Relish-mediated immune deficiency in the transgenic mosquito Aedes aegypti - Shin, Sang Woon (The National Academy of Sciences, 2003)
The lack of genetic means has been a serious limitation in studying mosquito immunity. We generated Relish-mediated immune deficiency (RMID) by transforming Aedes aegypti with the ΔRel transgene driven by the vitellogenin (Vg) promoter using the pBac[3xP3-EGFP, afm] vector. A stable transformed line had a single copy of the Vg-ΔRel transgene. The Vg-ΔRel transgene expression was highly activated by blood feeding, and transgenic mosquitoes were extremely susceptible to the infection by Gram-negative bacteria. This RMID phenotype was characterized by severely reduced postinfection levels of antimicrobial peptides genes, defensin and cecropin. Crossing the RMID line with the wild-type strain produced the same RMID phenotype, indicating its dominant nature, whereas crossing with the Vg-def transgenic line, in which Defensin A was activated by blood feeding, restored the immunity to Enterobacter cloacae.